Pengaruh Kepatuhan Wajib Pajak Terhadap Pelunasan Pajak Daerah : (Survey Terhadap Petugas Pemungut Pajak Hotel dan Restoran Dipenda Kota Ambon) - Putri Maharani Makatita; Abdullah Sanduan (Jurnal Administrasi Terapan, 2023)
This study aims to know, analyze and obtain empirical evidence about the effect of taxpayer compliance on regional tax settlement (Survey of hotel and restaurant tax collectors of the Ambon City Revenue Office)The independent variable in this study is taxpayer compliance. The dependent variable in this study is the payment of regional taxes. The data in this study is primary data obtained from the distribution of questionnaires directly to all hotel and restaurant tax collectors of the Ambon City Revenue Office and secondary data as support.The analysis model used to test the hypothesis is a quantitative analysis in the form of sampling, this analysis is based on data from 64 respondents of tax officers/employees of the Ambon City Regional Revenue Office through the distribution of questionnairesThe results of this study show that partially taxpayer compliance has a significant effect on regional tax settlement, in Ambon City..Keywords: taxpayer compliance, regional tax settlement